(untitled) (REMUNOM, 2024)
The objective of this study was to evaluate the profile of the properties of some producers in the western mesoregion of the state of Tocantins, considering management, infrastructure, and productive characteristics. For this purpose, information was collected from 31 dairy farms through a structured questionnaire in Microsoft Forms. The questionnaire addressed the socioeconomic aspects of the producers, herd characteristics, property structure, animal profile and feeding, as well as milking management and hygiene. The data analysis reveals a significant diversity in management practices and levels of technological advancement in dairy farms, directly reflecting on productivity and milk quality. The predominance of extensive systems, family labor, and low adoption of advanced technologies, such as mechanical milking and regular mastitis testing, indicates an urgent need for greater technical support for producers who use traditional methods. 86.88% of the properties lack technical assistance is a critical factor contributing to low productive efficiency and the sanitary vulnerability of herds, especially concerning the prevention and control of mastitis, one of the main causes of economic losses in dairy farming. On the other hand, the more technologically advanced properties demonstrate that the adoption of modern management practices and reproductive biotechnologies positively impacts production and animal health. Multivariate analysis identified three distinct management profiles among the producers: Group 1, with traditional practices and lower technological advancement; Group 2, with an intermediate level of technological intensification; and Group 3, which stands out for the adoption of advanced technologies, especially in sanitary and reproductive management. These results are essential for guiding public policies and technical guidance aimed at increasing productive efficiency and the sustainability of milk production systems in the western mesoregion of Tocantins.